Red blood cell sedimentation rate measurements in a high aspect ratio microchannel - Passos, Andreas; Louka, Marinos; Vryonidis, Charalampos; Inglezakis, Antonis; Loizou, Constantinos; Nikiphorou, Elena; Psarelis, Savvas; Kaliviotis, Efstathios (My University, 2022)
The erythrocyte sedimentation rate (ESR) test is commonly used in clinical practice for monitoring, screening and diagnosing pathological conditions and diseases related to the inflammatory response of the immune system. Several ESR techniques have been developed over the years improving the reliability, the precision and the duration of the measurement.
Keywords: Erythrocyte sedimentation rate (ESR); micro-ESR; microfluidics; point-of-care; surface tension driven flow